2019
DOI: 10.3892/mmr.2019.10840
|View full text |Cite
|
Sign up to set email alerts
|

CARD10 promotes the progression of renal cell carcinoma by regulating the NF‑κB signaling pathway

Abstract: Previous studies have demonstrated that the expression of CARD10 is closely associated with the occurrence of tumors, and its role is mainly to promote tumor progression by activating the transcription factor NF-κB. However, the signaling pathway in renal cancer remains unclear. The objective of the present study was to investigate the ability of caspase recruitment domain 10 (CARD10) to regulate the NF-κB signaling pathway and promote the progression of renal cell carcinoma (RCC). Expression of CARD10 in ACHN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…To this end, we explored The Cancer Genome Atlas (TCGA) database and analysed Disease/progression-free survival of PCa patients expressing high or low levels of CARD14 , BCL10 , and MALT1 . Because the CARD14-related protein CARD10 was previously reported to contribute to other epithelial carcinomas [ 21 , 22 , 23 , 24 ], we also analysed its expression in PCa. Patients with high CARD14 expression were found to have a significantly lower Disease/progression-free survival compared with patients with low CARD14 expression ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we explored The Cancer Genome Atlas (TCGA) database and analysed Disease/progression-free survival of PCa patients expressing high or low levels of CARD14 , BCL10 , and MALT1 . Because the CARD14-related protein CARD10 was previously reported to contribute to other epithelial carcinomas [ 21 , 22 , 23 , 24 ], we also analysed its expression in PCa. Patients with high CARD14 expression were found to have a significantly lower Disease/progression-free survival compared with patients with low CARD14 expression ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…MALT1 knockdown reduces proliferation, invasion, and migration in PCa cell lines, as well as attenuates xenograft tumour establishment in nude mice [ 19 , 20 ]. Although CARD11 and CARD10 have been previously shown to contribute to lymphoid malignancies and epithelial carcinomas, respectively [ 21 , 22 , 23 , 24 ], CARD14 signalling has so far been mainly studied in keratinocytes in the context of psoriasis [ 6 ]. However, elevated CARD14 expression is also observed in human epithelial cancers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANTXR2 is a membrane-bound molecule that can interact with LRP6. LRP6 is an important surface receptor in the Wnt/β–catenin pathway, and thus can affect osteoblastic activity [ 36 ]. In String database ( https://string-db.org ), we found that ANTXR2 and LRP6 had a co-expression relationship (Supplementary 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…LCK activates NF-κB signaling through tyrosine phosphorylation of IκBα [ 39 , 40 ]. CARD10 is closely associated with tumor development because of its role in promoting tumor progression by activating NF-κB [ 41 , 42 ]. However, CARD10 has also been identified as a novel target of CEBPE, an essential transcription factor required for granulocytic differentiation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%